Obligation To Ensure Safety In Organized Trip Contract comparative study with the French and English laws - Faleh, Raghad; Hasan, Jaleel (Journal of Legal Sciences, 2022)
This research raises the issue of the obligation to ensure safety as the most important obligation of tourism and travel companies in the organized trip contract، which is why a tourist chooses this type of trip، If the tourist aims for entertainment and pleasure، he seeks to be sponsored by the organized company to ensure his safe and healthy return home without any damage ، particularly physical damage  ، Although this commitment is important، it has not received the attention of the Iraqi legislator، so this research is based on an analytical  comparative based on Egyptian and French law as well as English law  ، The legislative experience of these States، as well as the views of the opinions of jurisprudence and  court judgements  have been presented، concluding to the need for Iraqi legislation regulating travel contracts in general and the obligation to ensure safety in particular because of its importance.